The Effectiveness of Tibolone Versus Intranasal Oestrogen Replacement Therapy on Serum Lipid Profile in Postmenopausal Women (Annals of Medical Research, 2021)
None
Keywords: Tibolone, İntranasal estrogen, Lipids